To actually give the example:<br><br>&gt; -- assuming that x and z are defined, and ys is the list<br>&gt; map (\y -&gt; f x y z) ys<br><br><div class="gmail_quote">On Mon, Sep 13, 2010 at 9:16 AM, Magnus Therning <span dir="ltr">&lt;<a href="mailto:magnus@therning.org">magnus@therning.org</a>&gt;</span> wrote:<br>
<blockquote class="gmail_quote" style="border-left: 1px solid rgb(204, 204, 204); margin: 0pt 0pt 0pt 0.8ex; padding-left: 1ex;"><div class="im">On Mon, Sep 13, 2010 at 14:03, Lorenzo Isella &lt;<a href="mailto:lorenzo.isella@gmail.com">lorenzo.isella@gmail.com</a>&gt; wrote:<br>

&gt; Dear All,<br>
&gt; Suppose you have the function<br>
&gt;<br>
&gt; f x y z = x*y +z<br>
&gt;<br>
&gt; and that you want to iterate it on a list<br>
&gt; z=[1,2,3,4], with<br>
&gt; x=4 and y=3<br>
&gt;<br>
&gt; then you would do the following<br>
&gt;<br>
&gt; map (f x y) z.<br>
&gt;<br>
&gt; Now consider the case in which the list is given by y e.g.<br>
&gt;<br>
&gt; y=[1,2,3,4], with<br>
&gt; x=4 and z=3.<br>
&gt;<br>
&gt; How can you iterate f on y (i.e. its second argument) while keeping x and y<br>
&gt; fixed?<br>
<br>
</div>Using a lambda expression (anonymous function) or through clever use of flip.<br>
<br>
/M<br>
<font color="#888888"><br>
--<br>
Magnus Therning                        (OpenPGP: 0xAB4DFBA4)<br>
magnus@therning.org          Jabber: magnus@therning.org<br>
<a href="http://therning.org/magnus" target="_blank">http://therning.org/magnus</a>         <a href="http://identi.ca" target="_blank">identi.ca</a>|twitter: magthe<br>
</font><div><div></div><div class="h5">_______________________________________________<br>
Beginners mailing list<br>
<a href="mailto:Beginners@haskell.org">Beginners@haskell.org</a><br>
<a href="http://www.haskell.org/mailman/listinfo/beginners" target="_blank">http://www.haskell.org/mailman/listinfo/beginners</a><br>
</div></div></blockquote></div><br><br clear="all"><br>-- <br><div dir="ltr"><div>          Alex R</div></div><br>